Innovative Technics of Managing Engineers' Global Competencies; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Khoreshok A. A. Aleksey Alekseevich; Zhironkin S. A. Sergey Aleksandrovich; Tyulenev M. A.; Barysheva G. A. Galina Anzelmovna; Blumenstein V. Yu.; Hellmer M. C.; Potyagaylov S. V. Sergey Vitalyevich (2016, 2016)
Title screen